A Brief Analysis of Radio Propagation Models for Long Term Evolution - Mingfeng Zhao (Dianxin kexue)
The accurate network planning and optimization was based on good radio propagation model for the particular wireless environment and specific frequency.Several types of LTE-based propagation models were reviewed under the three kinds of propagation model such as empirical model, semi-empirical model and deterministic model. A comparison was made between different proposed propagation models that would be used for the LTE. Further, attenuation loss for the different propagation models under the same conditions was listed. Lastly, a good propagation model choice strategy for the TD-LTE in dense urban scene was presented.